Training on Thin Plate Welding (SMAW 1G) for Potential Employees - Osmar Buntu Lobo (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
Childhood is a time when children learn through play, so it is essential to provide opportunities for them to play and experience learning through play. Kindergarten is a place for early education, intertwined with messages for the child's growth and development. Besides being a playground, it can offer benefits that may not be widely known. For example, a slide helps develop children's gross motor skills, and indirectly, they learn to queue, which also trains their social and emotional skills. A merry-go-round encourages children to socialize with peers and become more independent. The seesaw introduces children to the concept of balance and weight. Lastly, swings and rocking chairs, among the children's favorite activities, teach courage and the ability to estimate time, which is related to cognitive development. The outdoor playground facilities at TK Kuncup Harapan are mostly made of carbon steel, making them an ideal target for this Community Service Program (PKM). This program is unique because mechanical engineering skills can be beneficial in early childhood education (PAUD). Collaboration between the Department of Mechanical Engineering and PAUD is not often seen, which motivates the organizers to be excited and optimistic about carrying out this activity. There are several methods to join carbon steel, including riveted joints, bolted joints, and welded joints. Welding is considered a cost-effective and widely used method, especially in construction and steel frame applications. Based on the importance of educational play equipment and the observed damage to the playground at TK Kuncup Harapan, this proposal has been prepared to address the needs of the school. The goal of this service is to maintain (repair and restore) the playground equipment that has been damaged and is no longer usable. In addition to maintenance activities, this service will also provide basic welding training to potential teachers/staff so that any future issues involving carbon steel materials at the school can be resolved independently.